IMPLEMENTASI FUNGSI STRATEGI STRING OF PEARLS CHINA DI SAMUDERA HINDIA TAHUN 2005-2013 - Alby, Syahroni; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
China is one of the countries with rapid economic growth, economic growth continues to increase significantly in 2009 Since this country became a net importer of energy in the form of significant oil, nearly 60% of the domestic industry is an industry-energy-intensive manufacturing. China does not have sufficient natural resources to support the development and economic growth. To secure its energy supply needs in imports from the Middle East region, China using String Of Pearls strategy. This study investigates the ways in String Of Pearls strategy is implemented by China.This research is descriptive research that is based on the systematic patterns of thought, factual, and accurate, information on the facts and the properties of a particular population or area. While the data collection techniques used are library research.The research found that '' String Of Pearls strategy’' run by China in the Indian Ocean are implemented with the cooperation in the field of infrastructure development such as ports, airports, and subsea pipeline with countries in the path of China's energy transportation.Keywords : China, Implementation, Strategies, String Of Pearls